(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Two cases of multiple primary malignancies (two or more neoplasms without any relationship between them) are presented in this paper. The first case (65 years) was a male in whom follicular carcinoma of thyroid, metachronous neuroendocrine tumor of duodenum and urinary bladder transitional cell carcinoma were diagnosed within an eight-year period. The second case (65 years) was a female with synchronous dual malignancy of lung and urinary bladder diagnosed within a very short period of time.